Combining Marandu grass grazing height and supplementation level to optimize growth and productivity of yearling bulls - Barbero, R. P. [UNESP]; Malheiros, E. B. [UNESP]; Araújo, T. L.R. [UNESP]; Nave, R. L.G.; Mulliniks, J. T.; Berchielli, T. T. [UNESP]; Ruggieri, A. C. [UNESP]; Reis, R. A. [UNESP] (Elsevier, 2015)
Two experiments were conducted to determine the effects of grazing height and supplementation levels of Marandu pastures on average daily gain (ADG), gain per hectare (GPH) and methane (CH4) emissions during the wet season under continuous stocking by Nelore yearling bulls. Exp. 1: three grazing heights were evaluated: 15, 25 and 35 cm, combined with 0.3% of BW of a supplement (161 g crude protein (CP)/kg and 20.1 MJ gross energy (GE)/kg on dry matter basis (DMB)). Experimental design was completely randomized (three paddocks per treatment), and the effects were analyzed by polynomial orthogonal contrasts. Exp. 2: grazing heights were combined with decreasing supplementation levels as grazing heights increased: short height (15 cm) and high supplementation (0.6% of BW of a supplement: 142 g CP/kg and 18.9MJ GE/kg on DMB) (SHHS); moderate height (25 cm) and moderate supplementation (0.3% of BW of a supplement: 161 g CP/kg and 20.1MJ GE/kg on DMB) (MHMS) or tall height (35 cm) without supplementation) (THWS). Experimental design was completely randomized (three paddocks per treatment), and treatment means were compared by Tukey test (P<0.05). In Exp. 1, ADG increased linearly (P=0.02), and GPH decreased linearly (P=0.0002) as grazing height increased. Methane emission was not affected (P=0.64) by grazing height. In Exp. 2, ADG was not influenced (P=0.14) by treatments. However, GPH was the greatest (P<0.0001) for the SHHS treatment. In addition, CH4 emissions were lower (P<0.0001) in SHHS and MHMS bulls compared to THWS. The SHHS can improve the GPH without decreasing the ADG of each individual animal. Optimizing supplementation level according to grazing pressure may improve the nutrition efficiency on beef cattle production by decreasing the CH4/ADG and MJ CH4/MJ metabolizable energy intake.
Keywords: Beef cattle; Grazing height; Methane; Performance; Supplementation